2021
DOI: 10.24323/akademik-gida.1050746
|View full text |Cite
|
Sign up to set email alerts
|

An Optimization Study for Laboratory Scale Production of Glucose Syrup from Potato, Wheat and Maize Starch

Abstract: Glucose syrup is a valuable food ingredient produced by the hydrolysis of starch preferrably from maize. In this study, small-scale production process of glucose syrup from wheat, maize and potato starches was investigated. Two-step ezymatic hydrolysis using α-amylase and amyloglucosidase for liquefaction and saccharification, respectively, was analyzed based on the glucose content of a final product. The optimization of conditions was conducted with different initial amount of starch, different amount of enzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…After hydrolysis of stale bread powder under the optimal conditions, the FSY was 63.21±1.1% that was not significantly different from the predicted value of 62.49%. This value was lower than 97.04% obtained by Yilmaz et al (2021) and 59.8% reported by Sadaf et al (2021) using commercial enzymes. However, our result is close to the outcomes of Nwaga et al (2008) and Torabi et al (2021) who reported a yield of 67.8% and 69.8% respectively.…”
Section: Optimal Conditions For Fermentable Sugars Productioncontrasting
confidence: 63%
“…After hydrolysis of stale bread powder under the optimal conditions, the FSY was 63.21±1.1% that was not significantly different from the predicted value of 62.49%. This value was lower than 97.04% obtained by Yilmaz et al (2021) and 59.8% reported by Sadaf et al (2021) using commercial enzymes. However, our result is close to the outcomes of Nwaga et al (2008) and Torabi et al (2021) who reported a yield of 67.8% and 69.8% respectively.…”
Section: Optimal Conditions For Fermentable Sugars Productioncontrasting
confidence: 63%
“…The amylopectin is a branching chain polymer containing 95 % glucose connected by α-(1 -4) linkages while remaining 5 % via α-(1 -6) glycosidic bonds. The conversion of starch into individual glucose units involves the hydrolysis of these α-(1 -4) and α-(1 -6) linkages, which can be made possible by the action of acid (H 2 SO 4 /HCl) or enzymes (α-amylase and glucoamylase) (Bello-Perez et al, 2020;Kapar Yilmaz et al, 2021). To unravel the potential of BW as the sustainable feedstock, it should be subjected to pretreatment or hydrolysis for the breakdown of starch into monomeric fermentable sugars.…”
Section: Bread Waste Composition and Saccharification Processmentioning
confidence: 99%
“…The branching chain polymer known as amylopectin is composed of 95% glucose linked by α-(1 -4) linkages, with the remaining 5% connected by α-(1 -6) glycosidic bonds. The hydrolysis of these α-(1 -4) and α-(1 -6) linkages is necessary for the conversion of starch into discrete glucose units, and it can be accomplished by the action of an acid (H2SO4/HCl) or an enzyme (-amylase and glucoamylase) (18) (19).…”
Section: Bfrom Bread Waste To Bioethanol Productionmentioning
confidence: 99%